The fishery for pelagic redfish (Sebastes mentella) in the Irminger Sea and adjacent waters - Sigurdsson, Thorsteinn; Kristinsson, Kristján; Rätz, Hans-Joachim; Nedreaas, Kjell; Melnikov, Sergey P.; Reinert, Jakup (ICES Journal of Marine Science, 2006)
This paper describes the pelagic fishery for deep-sea redfish, Sebastes mentella, in the Irminger Sea and adjacent waters, from the start of commercial exploitation of the resource in 1982. The information prior to 1990 is mostly based on ICES reports and unpublished data, but from 1990, logbook data from a joint database on a haul-by-haul basis from the Faroe Islands, Germany, Greenland, Iceland, Norway, and Russia are used to describe the fishery. The nations listed are the main ones operating on the resource, catching about 80% of the total reported catches in recent years. The logbook data include inter alia information on positions, catch, and trawling time. Additionally, some nations also include information on gear type and size of gear used, and in some cases also trawling depth. Length distributions of commercial catches from various fleets for the whole period have also been collected, and are shown along with information on the mean lengths in the catches for the whole period. The paper therefore provides a detailed overview of the fishery in terms of area, season, depth, and size composition of the catches from the start of the pelagic fishery to the present, allowing better understanding of the behaviour of the fishery and, in turn, providing improved background for assessment of the resource in the future.